2017
DOI: 10.1093/cercor/bhx116
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte- and Neuron-Specific Nogo-A Restrict Dendritic Branching and Spine Density in the Adult Mouse Motor Cortex

Abstract: Nogo-A has been well described as a myelin-associated inhibitor of neurite outgrowth and functional neuroregeneration after central nervous system (CNS) injury. Recently, a new role of Nogo-A has been identified as a negative regulator of synaptic plasticity in the uninjured adult CNS. Nogo-A is present in neurons and oligodendrocytes. However, it is yet unclear which of these two pools regulate synaptic plasticity. To address this question we used newly generated mouse lines in which Nogo-A is specifically kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 58 publications
0
38
0
Order By: Relevance
“…As the mice used in this study had global deletion of Nogo-A, we cannot rule-out possible effects from altered glia cells. Indeed, a recently study by Zemmar et al[ 41 ] showed that both neuronal and oligodendrocyte-localized Nogo-A regulate dendritic branching in cortical neurons. Interestingly, the two had compartmentalized effects, with oligodendrocytic Nogo-A regulating distal dendrites and neuronal Nogo-A modulating more proximal dendrites.…”
Section: Discussionmentioning
confidence: 99%
“…As the mice used in this study had global deletion of Nogo-A, we cannot rule-out possible effects from altered glia cells. Indeed, a recently study by Zemmar et al[ 41 ] showed that both neuronal and oligodendrocyte-localized Nogo-A regulate dendritic branching in cortical neurons. Interestingly, the two had compartmentalized effects, with oligodendrocytic Nogo-A regulating distal dendrites and neuronal Nogo-A modulating more proximal dendrites.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, anti-NogoA antibody treatment also demonstrated that in an uninjured system, inhibition of the Nogo pathway induced sprouting of CA3 fibers [ 86 ]. In a study by Zemmar and colleagues, mouse lines in which Nogo-A was knocked out in either oligodendrocytes or neurons revealed enhanced dendritic branching and spine formation, suggesting that both sources of Nogo-A contribute to synaptic development and plasticity [ 87 ].…”
Section: Myelin In the Nervous Systemmentioning
confidence: 99%
“…It is then plausible that either: (1) the limitation of myelin debris enriched with Nogo-A, initiating signaling through the NgR1-dependent phosphorylation of CRMP2 (inflammatorymediated demyelination and secondary axonal damage; outside-in axonopathy), preserves axons or; (2) limiting the phosphorylation of CRMP2 within the axon prevents myelin from degenerating (inside-out axonal damage; secondary demyelination) and abrogates the cycle of inflammatory cell infiltration within the CNS. These outside-in versus inside-out mechanisms of axonopathy still require investigation, particularly because Nogo-A is also highly expressed in axons and may play an active role in driving degeneration during neuroinflammation (Ineichen et al, 2017;Zemmar et al, 2018). Although neuronal Nogo-Adependent signaling downstream to CRMP2 has not been well defined but has been identified in the regulation of axonal transport (Joset et al, 2010).…”
mentioning
confidence: 99%